Using SimulATe to model the effects of antibiotic selective pressure on the dynamics of bacterial populations - David, Pedro H.C. (2021)
Antibiotics are notable weapons in fighting bacteria. Nowadays, however, the effectiveness of antibiotics is severely hindered by the increasing levels of antibiotic resistances in pathogenic bacterial populations, which can persist due to the selective pressure caused by antibiotic exposure. Arguably, the main cause of antibiotic resistances endurance in nature is antibiotic misuse, such as via overusing, inappropriate prescribing as well as the uncontrolled use in agriculture and livestock. There is also a lack of knowledge on appropriate antibiotic usage by the general public. Public scientific literacy and more research on therapeutic practices are fundamental to tackle this problem. Here, we present SimulATe a software which allows the simulation of the effects of antibiotic therapies on bacterial populations during human infections. This software can be used to develop students’ scientific literacy, using infections and antibiotic treatments as context to engage students in scientific practices, and discussions on antibiotic treatment onset and duration or on its use in immunosuppressed or critically ill individuals. SimulATe’s features also allow it to be used for research purposes allowing the simulation of real scenarios and exploration of their outcomes across the parameters’ landscape.